Technology adoption and the investment climate : firm-level evidence for Eastern Europe and Central Asia - Corrêa, P. H. da Rocha (Policy research working paper, 2008)
"The international diffusion of technology presents an opportunity for developing economies distant from the world technological frontier to reduce their income gap relative to advanced economies. It is therefore crucial to understand why, when faced with similar technological alternatives different firms in different countries choose to adopt different vintages of capital. This paper examines technology adoption across firms in Eastern Europe and Central Asia. The findings show that access to complementary inputs - managerial capacity, skilled labor, finance, and good infrastructure - and to international knowledge - through foreign direct investment or exports - is an important correlate of technology adoption. The link between market incentives and technology adoption is more nuanced. Although consumer pressure results in technology adoption, competitor pressure does not, suggesting that only firms with rents are able to adopt technology given substantial resource constraints. Privatized firms exhibit better technology adoption outcomes but only when a clear private owner with a profit incentive is present. Better governance is associated with technology adoption only in the countries that joined the European Union in 2004. Future increases in technology adoption by firms in the region will require complementary reforms of the investment climate. "--World Bank web site